The 7P Marketing Mix Strategy in Building the Image of Inclusive Education at MAN 2 Sleman Yogyakarta - Pratama, Yoga Anjas; Hasanah, Uswatun; Yuliati, Retno; Agung, Putry; Nabilla, Nabilla (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
Marketing mix strategies can increase interest, attractiveness, and build the image of educational institutions. MAN 2 Sleman, Yogyakarta, is the first madrasah to implement inclusive education and has become a model for its implementation. This study aims to examine the implementation of the 7P marketing mix strategy at MAN 2 Sleman, with the results contributing positively to the development of the madrasah and serving as a reference for other educational institutions in building an inclusive education image. This is a descriptive, qualitative study that utilizes data collection tools such as interviews, observations, and documentation. The data obtained were analyzed using Miles and Huberman's data analysis model, which includes data reduction, data presentation, conclusion and verification. To test the validity of the data, data triangulation was then carried out. The results of this study are: (1) MAN 2 Sleman has implemented the 7P marketing mix strategy in building an inclusive education image (2) The implementation of the 7P marketing mix strategy can build an inclusive education image, with the following impacts: increased public trust, increased number of inclusive students, external recognition of MAN 2 Sleman as an inclusive education provider, and strengthened school reputation and image at the regional, national, and international levels. Keywords: Marketing Mix Strategy, Marketing Mix, Inclusive Education, Madrasah Image